What Type of Food Can Older Adults Masticate?: Evaluation of Mastication Performance Using Color-Changeable Chewing Gum - Wada, Shinichi (Dysphagia, 2017)
This study determines if older adults can masticate regular foods via a simple test conducted using a color-changeable chewing gum. Seventy-nine consecutive inpatients of our clinic receiving rehabilitation and general medicine were assessed for eligibility. The inclusion criterion was >65 years. Thirty patients consented to participate. The main outcome variable was the food bolus texture at the swallowing threshold for five regular foods. The main explanatory variable was the a* value of the color-changeable chewing gum after 120 s of chewing (a* represents the degree of color between red and green, and a positive a* value indicates red). The mean age ± standard deviation of the participants was 81.6 ± 8.6 years, and 40% were men. Participants being able to prepare the food with suitable texture for swallowing was positively associated with the a* values in boiled rice, ginger-fried pork loin, boiled fish-paste, and rice cracker (Crude OR 1.18, 1.15, 1.17, and 1.50; P < 0.001, = 0.026, <0.001, and <0.001, respectively). The cut-off a* values had markedly high specificities (1.0) for boiled rice and boiled fish-paste and high sensitivities (0.86–0.94) for three foods, except boiled rice. We believe that mastication evaluation using the color-changeable chewing gum is not only useful but also extremely practical, even for older adults in a wide range of settings, including an individual’s home. This approach would lead to a reduction in unnecessary mechanically altered or pureed food for older adults who can eat pureed food and safely provide palatable food.